2013
DOI: 10.1007/s10342-013-0776-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the regeneration of compacted forest soils by planting black alder in skid lane tracks

Abstract: Soil compaction due to the use of heavy machinery for timber harvesting has become a widespread problem in forestry. However, only few studies deal with the regeneration of compacted forest soils. In the present study, we examined the potential of accelerating soil regeneration by planting black alder trees (Alnus glutinosa (L.) Gaertn.) in skid lane tracks. In 2003, seedlings were planted into the rut beds of severely compacted skid lanes in two Swiss forest sites. In addition, some of the ruts were filled wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 53 publications
2
29
1
Order By: Relevance
“…This mid-term recovery of soil structure, step by step, overlaid the increasing root respiration. Meyer et al (2014) observed a similar regeneration effect in terms of an enhanced soil aeration by planting black alder. These findings correspond to results obtained by our first linear mixed-effect model (Eq.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…This mid-term recovery of soil structure, step by step, overlaid the increasing root respiration. Meyer et al (2014) observed a similar regeneration effect in terms of an enhanced soil aeration by planting black alder. These findings correspond to results obtained by our first linear mixed-effect model (Eq.…”
Section: Discussionsupporting
confidence: 52%
“…Some tree species can penetrate with their root systems compacted soils and consequently create pathways for gas exchange. While Meyer et al (2014) observed an increasing macroporosity and air conductance in skid trails planted with black alder (Alnus glutinosa; (L.) Gaertn. ), Gaertig et al (2002) showed that the ability of oaks (Quercus petraea; (Matt.)…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The remediation and reclamation of compacted forest soils can be achieved by accelerating the soil physical and biological features with some artificial measures such as earthworms inoculation [18], seedling plantation [27,28], and mulching [10]. Natural processes such as the root-soil interactions, the expansion-retraction of clay particles, the freezing-thawing of water in soil, and the activities of soil biota can also support, to a certain degree, the natural restoration of compacted soil properties [21,29].…”
Section: Introductionmentioning
confidence: 99%
“…According to Murat (2002), Alnus trees may be planted as part of silvicultural treatments and phytomelioration, mostly in pine stands, as well as in the process of reconversion of degraded soils. Due to their constant demand for nutrients and a rapid growth rate, Alnus species are used as pioneer plants for the stabilization of river banks (Meyer et al 2014) and the reclamation of wetland sites, many of which have dried up in recent years (Beatty et al 2015). Of the three species mentioned above, the most highly valued one is the black alder as it can fix nitrogen from the atmosphere with the process of symbiosis with Frankia bacteria (Bond et al 1954).…”
Section: Introductionmentioning
confidence: 99%